2017
DOI: 10.1364/oe.25.008158
|View full text |Cite
|
Sign up to set email alerts
|

Thin high numerical aperture metalens

Abstract: We designed, fabricated, and characterized a thin metalens in an amorphous silicon film of diameter 30 µm, focal length equal to the incident wavelength 633 nm. The lens is capable of simultaneously manipulating the state of polarization and phase of incident light. The lens converts a linearly polarized beam into radially polarized light, producing a subwavelength focus. When illuminated with a linearly polarized Gaussian beam, the lens produces a focal spot whose size at full-width half-maximum intensity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 18 publications
0
15
1
1
Order By: Relevance
“…Meta-optics have the advantage of extreme form birefringence, which enable them to manipulate the polarization states of light in unique manners. A few illustrative examples of these advantages are in polarimetric imaging [31], high-efficiency polarizers [32] and polarization sensitive optics [33]. Additionally, their sub-wavelength dimensions are extremely useful in integrated optics and photonics, where integration density is a critical parameter for technology adoption [34][35][36].…”
Section: Figure 3: Broadband Mdls Design (A-c) and Simulated Point-smentioning
confidence: 99%
“…Meta-optics have the advantage of extreme form birefringence, which enable them to manipulate the polarization states of light in unique manners. A few illustrative examples of these advantages are in polarimetric imaging [31], high-efficiency polarizers [32] and polarization sensitive optics [33]. Additionally, their sub-wavelength dimensions are extremely useful in integrated optics and photonics, where integration density is a critical parameter for technology adoption [34][35][36].…”
Section: Figure 3: Broadband Mdls Design (A-c) and Simulated Point-smentioning
confidence: 99%
“…A method for designing metalenses in a thin amorphous silicon film for the visible light spectrum was described in [ 23 ]. Briefly, it is as follows.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The design of the metalens based on a spiral phase plate for the incident circularly polarized light was considered in detail in [ 23 ]. In this work, we design an SZP and a corresponding metalens that can generate two optical vortices with topological charges 1 and 2.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Despite of exciting progresses in plasmonic metaholograms, the low‐efficiency issue of transmissive plasmonic metasurfaces for visible light still hinders their practical applications. It is this reason that stimulates the rapid developments of all‐dielectric metaholograms . Recently, Faraon and co‐workers reported that a polarization‐switchable phase hologram can generate two different patterns for two orthogonally polarized LP lights .…”
Section: Applicationsmentioning
confidence: 99%